To click or not to click – The importance of understanding the layers of the forehead when injecting neuromodulators – A clinical, prospective, interventional, split‐face study. (8th December 2020) - Davidovic, Kristina; Melnikov, Dmitry V.; Frank, Konstantin; Gavril, Diana; Green, Jeremy B.; Freytag, David L.; Heisinger, Stephan; Pavicic, Tatjana; Gold, Michael H.; Cotofana, Sebastian
Abstract: Background: Differences in the effectiveness of neuromodulator treatments for horizontal forehead lines dependent on depth of product administration have been described. However, knowledge in respect to the fascial anatomy of the forehead still remains elusive. Aims: To relate the fascial anatomy of the forehead to the effectiveness of neuromodulator treatments by conducting a clinical, prospective, interventional split‐face study in which injections for the treatment of horizontal forehead lines are performed differently between facial sides. Methods: This study included a total of n = 14 patients with a mean age of 35.71 (7.8) years and mean body mass index of 21.9 (3.0) kg/m 2 . One side of the forehead was injected superficially by positioning the product in the superficial fatty layer, whereas the contralateral side was injected deep targeting the supraperiosteal plane (random selection). The treatment outcome was rated by the physician and by two independent observers according to a forehead line severity scale (0‐4) at 14 and at 30 days. Results: All three observers agreed in their ratings (ICC: 0.942) that the deep injection technique resulted in a superior outcome: D14 (superficial vs deep) 0.17 (0.4) vs 0.14 (0.4; P  = .583) at rest and 1.26 (0.6) vs 0.43 (0.5; P  < .001) for frontalis contraction; D30 0.17 (0.4) vs 0.14 (0.3) at rest ( P  = .583) and 1.21 (0.6) vs 0.43 (0.5; P  < .001) for frontalis contraction. Conclusion: The results of this study underscore how detailed anatomic knowledge can enhance results of aesthetic interventions, in this case horizontal forehead line treatment with neuromodulators.